Prehistoric trepanation in the Cuzco region of Peru: A view into an ancient Andean practice - Andrushko, Valerie A.; Verano, John W. (American Journal of Physical Anthropology, 2008)
In this study, patterns of prehistoric trepanation in the southern highlands of Peru were examined through an analysis of 11 Cuzco-region burial sites. Trepanations were found in 66 individuals, with several individuals exhibiting more than one trepanation, for a total of 109 perforations observed. The predominant methods used were circular cutting and scraping-methods that proved highly successful with an overall 83% survival rate and little ensuing infection. Survival rates showed a significant increase over time, apparently reflecting improvements in trepanation technique through experimentation and practical experience. Practitioners avoided certain areas of the cranium and employed methods that reduced the likelihood of damage to the cerebral meninges and venous sinuses. In many cases, trepanation as a medical treatment appears to have been prompted by cranial trauma, a finding that corroborates other studies pointing to cranial trauma as a primary motivation for the surgical procedure.
Keywords: *Skull/su [Surgery]; *Trephining/hi [History]; Cranial trauma; Culture; Cuzco; History, Ancient; Humans; Inca; Paleopathology; Peru; Skull; Skull Fractures; Skull Fractures/hi [History]; Skull Fractures/su [Surgery]; Skull/pa [Pathology]; Treatment Outcome; Trepanation; Trephining; Trephining/is [Instrumentation]; Trephining/mt [Methods]; Wounds and Injuries; Wounds and Injuries/hi [History]; Wounds and Injuries/su [Surgery]; adult; aged; article; controlled study; dept.ant; experimentation; female; head injury; human; human tissue; male; meninx; peer-reviewed; prehistoric period; school child; sinus venosus; skull; surgical technique; survival rate; trepanation